Pelatihan Pengelolaan Stres Berbasis Mindfulness untuk Meningkatkan Profesionalitas Guru dalam Proses Pengajaran: Mindfulness-Based Stress Management Training to Enhance Teacher Professionalism in the Teaching Process - Rahmah, Dian Dwi Nur; Purnomo, Raihan Jouras Zidan; Tesalonika, Clara; Khairiah, Aisyah; Firjatullah, Firjatullah (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Stress management is an important skill that educators need to possess to plan and implement the learning process, assess learning outcomes, provide guidance and training, as well as engage in research and community service. The purpose of this training is to enhance stress management skills to improve the teaching process of educators. The training was conducted for teachers at SMA Negeri 16 Kota Samarinda and was attended by 13 participants. The methods used in this training include Training Need Analysis (TNA), training modules, material delivery, discussions, mindfulness, and pre-test and post-test evaluations. The results of this training show an improvement in understanding stress management. This improvement was obtained from data collected through pre-tests and post-tests, revealing an increase of 17%.